Stakeholder engagement in diabetes self-management: patient preference for peer support and other insights - Kwan, Bethany M; Jortberg, Bonnie; Warman, Meredith K; Kane, Ilima; Wearner, Robyn; Koren, Romona; Carrigan, Thomas; Martinez, Vincent; Nease, Donald E (Family practice, 2017)
Self-management support (SMS) for patients with diabetes can improve adherence to treatment, mitigate disease-related distress, and improve health outcomes. Translating this evidence into real-world practice is needed, as it is not clear which SMS models are acceptable to patients, and feasible and sustainable for primary care practices. To use the Boot Camp Translation (BCT) method to engage patient, practice, community resource and research stakeholders in translation of evidence about SMS and diabetes distress into mutually acceptable care models and to inform patient-centred outcomes research (PCOR). Twenty-seven diabetes care stakeholders, including patients and providers from a local network of federally qualified health centres participated. Stakeholders met in-person and by conference call over the course of 8 months. Subject matter experts provided education on the diabetes SMS evidence. Facilitators engaged the group in discussions about barriers to self-management and opportunities for improving delivery of SMS. BCT participants identified lack of social support, personal resources, trust, knowledge and confidence as barriers to diabetes self-management. Intervention opportunities emphasized peer support, use of multidisciplinary care teams and centralized systems for sharing information about community and practice resources. BCT informed new services and a PCOR study proposal. Patients and family engaged in diabetes care research value peer support, group visits, and multidisciplinary care teams as key features of SMS models. SMS should be tailored to an individual patient's health literacy. BCT can be used to engage multiple stakeholders in translation of evidence into practice and to inform PCOR.